2013
DOI: 10.1371/journal.pone.0054535
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Consistency: Individual versus Population Variation in Annual-Cycle Schedules of a Long-Distance Migrant Bird

Abstract: Flexibility in scheduling varies throughout an organism’s annual cycle, reflecting relative temporal constraints and fitness consequences among life-history stages. Time-selection can act at different scales, either by limiting the range of alternative strategies in the population, or by increasing the precision of individual performance. We tracked individual bar-tailed godwits Limosa lapponica baueri for two full years (including direct observation during non-breeding seasons in New Zealand and geolocator tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 53 publications
4
152
0
1
Order By: Relevance
“…Ecological studies of migratory birds also echo the findings on chronotypes described above for chronobiology (figure 3). Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 68%
See 1 more Smart Citation
“…Ecological studies of migratory birds also echo the findings on chronotypes described above for chronobiology (figure 3). Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 68%
“…[150]). It can be estimated as the proportion of variance within individuals relative to the overall variance measured within a population (ranging from 1 ¼ fully repeatable to 0 ¼ not repeatable; but see [95] for caveats). Traits that show high repeatability, and whose repeatability is to a large extent genetic or epigenetic, are labile to evolutionary changes to the mechanisms that determine their expression.…”
Section: (B) Chronotypementioning
confidence: 99%
“…Repeatability is the fraction of total phenotypic variance that could be attributed to the individual, and thus can be affected by how consistent individuals are and the amount of phenotypic variance present (see e.g. Conklin et al 2013). For females, repeatability between combinations of consecutive years was largely explained by how consistent arrival was in individuals, suggesting that under some circumstances individuals could not express their normal individual schedule, resulting in low repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Repeatability describes how consistently individuals differ from each other (Conklin et al 2013), which depends on how consistent individuals are, and how large differences are between individuals (total phenotypic variation). Low repeatabilities could thus be a result of low consistency within individuals, or alternatively through low variation among individuals.…”
Section: Analysesmentioning
confidence: 99%
“…Furthermore, the choice of a certain wintering area and migratory strategy may affect annual schedules including timing of events at breeding area (Marra et al 1998), which demonstrates the importance to follow individuals throughout the annual cycle. Knowledge of variation in migratory routines within and between individuals of a population is also important to understanding and predicting the ability of species responses to environmental change, including climate change (Conklin et al 2013).We employed GLS (Global Location Sensing, also called 'light-level geolocation' or just 'geolocation') technique based on the analysis of diurnal changes in light levels to track annual movements of northern lapwings (Vanellus vanellus; here synonymously termed 'lapwing(s)'). Archival tags ('geolocators') record light intensities to determine dusk and dawn times from which geographical positions (two fixes daily) are calculated; day (night) length determines the latitude and time of local midday (midnight) the longitude (Hill 1994).…”
mentioning
confidence: 99%